1995
DOI: 10.1042/bj3050725
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a substrate site for transglutaminases on the human protein synthesis initiation factor 5A

Abstract: Protein synthesis initiation factor 5A (eIF-5A) from human erythrocytes was found to be a substrate for both plasma transglutaminase (Factor XIIIa) and guinea pig liver transglutaminase (GPLTG). When purified eIF-5A was incubated with GPLTG or Factor XIIIa in the presence of succinylated beta-casein, a covalent complex was identified. By isolating and analysing the product of the transglutaminases (TGases) reaction, the site of modification on eIF-5A has been identified as the unique amino acid hypusine. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 21 publications
0
30
0
1
Order By: Relevance
“…Future studies should clarify by which mechanism GC7 is able to promote autophagy. In keeping with this assumption it is interesting to note that hypusine of the eIF-5A chain functions as an acyl acceptor substrate for transglutaminases (Beninati et al 1995). Considering the structural similarity between hypusine molecule and GC7, it would be interesting to study whether this polyamine analogue can act as a substrate of Type 2 transglutaminase transamidating activity which has been shown to play an important role in the recruitment of ubiquitinated proteins into the autophagosomes (D'Eletto et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should clarify by which mechanism GC7 is able to promote autophagy. In keeping with this assumption it is interesting to note that hypusine of the eIF-5A chain functions as an acyl acceptor substrate for transglutaminases (Beninati et al 1995). Considering the structural similarity between hypusine molecule and GC7, it would be interesting to study whether this polyamine analogue can act as a substrate of Type 2 transglutaminase transamidating activity which has been shown to play an important role in the recruitment of ubiquitinated proteins into the autophagosomes (D'Eletto et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This intermediate is not accumulated in cells but is immediately hydroxylated at C-2 of the incoming 4-aminobutyl moiety to form hypusine (Abbruzzese et al, 1985(Abbruzzese et al, , 1986(Abbruzzese et al, , 1988b. More recently it was found that eIF-5A undergoes a post-translational modification catalyzed by transglutaminase (Beninati et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In order to modify the intracellular level of a radioactive polyamine reaching a suitable specific radioactivity, it may be useful to perform the incubation of the cells with the polyamine whose conversion rate is lower. A mixture of two radiolabelled polyamines has proved to be applicable for this type of incubation study [23].…”
Section: Effects Of Intracellular Polyamines Pool On the Detection Ofmentioning
confidence: 99%